The role of job insecurity in emotional exhaustion and work engagement during the COVID-19 pandemic: the moderating effect of organizational reward and care policies (El papel de la inseguridad laboral en el agotamiento emocional y el compromiso laboral durante la pandemia de la COVID-19: el efecto moderador de la recompensa organizacional y las políticas de cuidado). Issue 1 (2nd January 2022) - Tsai, Hung-Yu
ABSTRACT: This study developed and tested a moderation model to investigate the effects of job insecurity due to the coronavirus disease of 2019 (COVID-19). We hypothesized that reward and care policies can moderate the relationship between job insecurity due to COVID-19 and employee outcomes (i.e., emotional exhaustion and work engagement). Two-wave data were collected from 344 worker–manager pairs in China, demonstrating that job insecurity negatively affects work engagement. Conversely, job insecurity had a significant positive effect on emotional exhaustion. Another finding was that the reward policy was less negatively related to job insecurity due to COVID-19 than employees' work engagement. Moreover, care policy was related less positively to job insecurity due to COVID-19 than to employees' emotional exhaustion.